ONTOLOGI RIBA DALAM HADIS (Kajian Tematik Hadis Ahkam) - Edy Saputra (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2021)
This article contains a thematic study of Ahkam's hadith on the ontology of riba. This study is included in the library research category. The study method used is descriptive analytical. Primary data in this study came from nine primary hadith books, namely Al-Kutub Al-Tis'ah consisting of Sahih Al-Bukhari, Sahih Muslim, Sunan Abu Daud, Sunan Al-Tirmizi, Sunan Al-Nasa'I, Sunan Ibn Majah. , Muwatha 'Malik, Sunan Al-Darimi, and Musnad Ahmad. As for data collection techniques, the author uses the android application "Jami 'Al-Kutub Al-Tis'ah" from the Arabia for Information & Technology institute. The results of this study indicate that riba can be mapped into two classifications; riba al-Ba'i and riba of al-Duyun. The categorization of riba into these two types is a simple and simple division. If riba occurs in a buying and selling transaction, it is called riba al-Ba'i. Furthermore, if riba occurs in accounts payable transactions, it is called riba al-Duyun. Then not all buying and selling occurs riba, and not all accounts payable transactions are considered riba.